Efficacy of Topical Hydrocortisone in Combination with Topical Ciclosporin A for the Treatment of Dry Eye Disease in Patients with Sjögren Syndrome. (30th November 2021) - Fondi, Klemens; Miháltz, Kata; Vécsei-Marlovits, Pia Veronika
Abstract : Introduction . The aim of this randomized, observer-masked, parallel group study was to evaluate the short-term and long-term effects of topical hydrocortisone administered in addition to topical ciclosporin A for the first 2 weeks of the treatment in patients with dry eye disease associated with Sjögren syndrome. Materials and Methods . 24 eyes of 12 patients with severe dry eye disease associated with Sjögren syndrome were included in this study. Both eyes of all patients were treated with preservative-free Ciclosporin A eye drops once daily for 6 months. Additionally, one eye of each patient received hydrocortisone eye drops three times daily for the first two weeks of treatment. The study parameters were assessed before treatment, after 2 weeks, and after 6 months of treatment. Results . Tear BUT and corneal fluorescein Oxford staining grade showed significant differences with respect to the baseline when treated with ciclosporin A and hydrocortisone (CsA + Hc) and a nonsignificant increase when treated with ciclosporin A (CsA) alone. After 6 months of treatment, significant increases of tear BUT and corneal Fluorescein Oxford staining grade compared to baseline could be observed in both treatment groups. Aberrometry measurements showed significantly increased optical image quality after 6 months in the CsA + Hc group, while no significant changes could be detected in the eyes treated with CsA alone. However, no significant differences between the two treatment groups could be detected. Discussion . This study indicates that hydrocortisone combined with ciclosporin A therapy may provide fast improvement of clinical symptoms and could have long-term positive effects on the optical image quality in severe DED patients with Sjögren syndrome.